Maritime Awareness in IPAS Subjects Using TPACK Assisted Discovery Model for Elementary School Students - Ruciana Galunggung; Abdur Rofiq; Anda Prasetyo Ery (Politeknik Pariwisata Makassar, 2024)
Science and Social (IPAS) program offers a unique opportunity for students to engage with subject matter that is closely aligned with their daily lives. The IPAS program is designed to provide students with a comprehensive understanding of geographical conditions, ecosystems, and the surrounding environment. The program's objective is to provide students with an initial understanding of the potential wealth of Indonesia's natural resources in both agrarian and maritime fields. To facilitate this comprehension, educators must construct curricula that are malleable and situated within the real-world contexts of their students' lives, thereby rendering learning more meaningful. The objective of this research is to develop IPAS learning using the Discovery model with the assistance of TPACK, in order to facilitate the accommodation of students' diverse learning needs and the internalization of maritime awareness in their daily lives. This research was conducted using the research and development (R&D) method, employing the Lee & Owen model, which encompasses the following stages: needs assessment and front-end analysis, design, development, implementation, and evaluation. The trial design utilized in this development research consisted of a single group of 30 students from SDI Aisyiyah Jatinom, Blitar. The results of the trial demonstrate that the developed product meets the criteria for moderate effectiveness. This can be evidenced by the more active and explorative learning process, whereby students proactively offer opinions on the problems presented. Furthermore, the results of in-depth observations and interviews regarding the meaningfulness of maritime learning using the TPACK-assisted Discovery model are also discussed.